Anticipation of Indonesian Embargo Sanctions in the Economic Aspect of State Defense - Pasaribu, Charles; Saputro, Guntur Eko; Prakoso, Lukman Yudho (Journal of Social Work and Science Education, 2023)
National defense needs to be built to deal with threats that come from within and outside the country, this requires meeting the needs of the military in carrying out its functions, one of these needs is defense equipment but these needs cannot be fulfilled alone but still rely on other countries. This poses a threat if at any time you get an embargo sanction. The purpose of this study is to analyze the Anticipation of Indonesian Embargo Sanctions in the Aspect of National Defense. The research method uses qualitative research methods with a qualitative descriptive design. The results of the study show that the steps to anticipate government embargo sanctions have taken several things including realizing defense independence by empowering the domestic Defense Industry, as well as Confidence Building Measure Diplomacy to create mutual trust with other countries as well as carrying out diversification policies aimed at creating variations in meeting defense needs.